Revisiting the Reception of Gaudium Et Spes’s Vision of the Church-World Relationship - Gaut, Wilibaldus; Agustin, Jr, Danilo (Asian Horizons, 2025)
This year, 2025, marks the 60th anniversary of Gaudium et Spes, Vatican II’s Pastoral Constitution on the Church in the Modern World. As one of the landmark documents of the Second Vatican Council, it is renowned for articulating a vision of the Church’s openness to the world—an aspect widely regarded as a hallmark of the Council. However, the post-conciliar reception of this vision has generally been characterized by two contrasting attitudes. On the one hand, this openness is seen positively as a necessary step for the Church to engage more meaningfully with the contemporary world. On the other hand, it has been viewed as an overly optimistic stance that risks relativizing the Christian faith. In this article, by rereading Gaudium et Spes, we propose that these two perspectives need not be understood as opposing positions. Even if the document’s worldview may appear excessively optimistic, it does not necessarily lead to relativism. Rather, the Church’s more dialogical engagement with the world should be welcomed so long as it remains rooted in Gospel values and the faithful proclamation of the truth. In other words, the dialogical and the kerygmatic approaches are not mutually exclusive; they can—and must – complement each other.